2021
DOI: 10.1007/s10936-021-09804-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Predictability During Negation Processing in Truth-Value Judgment Tasks

Abstract: In experiments investigating the processing of true and false negative sentences, it is often reported that polarity interacts with truth-value, in the sense that true sentences lead to faster reaction times than false sentences in affirmative conditions whereas the same does not hold for negative sentences. Various reasons for this difference between affirmative and negative sentences have been discussed in the literature (e.g., lexical associations, predictability, ease of comparing sentence and world). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(53 reference statements)
0
5
2
Order By: Relevance
“…Participants saw visual contexts (e.g., a white square and a blue circle) followed by corresponding sentences (e.g., The square is (not) white/blue) whose predictability was varied depending on whether the two geometrical shapes differed in one (e.g., color; high predictability) or two aspects (color and pattern; low predictability). In contrast to Nieuwland (2016), where the typical truth by polarity interaction pattern was only observed for the conditions where critical nouns had low cloze probability values, in Rück et al (2021) the interaction was more pronounced for the high-predictable compared to the low-predictable condition. The authors suggest that different measures, such as response times or the N400, might reflect different mechanisms and stages of processing and, in particular, may be differently sensitive to predictability.…”
Section: Introductioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Participants saw visual contexts (e.g., a white square and a blue circle) followed by corresponding sentences (e.g., The square is (not) white/blue) whose predictability was varied depending on whether the two geometrical shapes differed in one (e.g., color; high predictability) or two aspects (color and pattern; low predictability). In contrast to Nieuwland (2016), where the typical truth by polarity interaction pattern was only observed for the conditions where critical nouns had low cloze probability values, in Rück et al (2021) the interaction was more pronounced for the high-predictable compared to the low-predictable condition. The authors suggest that different measures, such as response times or the N400, might reflect different mechanisms and stages of processing and, in particular, may be differently sensitive to predictability.…”
Section: Introductioncontrasting
confidence: 67%
“…Other studies have also shown that the processing load related to negation appears to be significantly reduced if the context licenses the use of negation in a sentence (Dale, 2011;Glenberg et al, 1999;Tian et al, 2010Tian et al, , 2016. Rück et al (2021) investigated the role of the predictability for the truth by polarity interaction in response times. Participants saw visual contexts (e.g., a white square and a blue circle) followed by corresponding sentences (e.g., The square is (not) white/blue) whose predictability was varied depending on whether the two geometrical shapes differed in one (e.g., color; high predictability) or two aspects (color and pattern; low predictability).…”
Section: Introductionmentioning
confidence: 99%
“…We reason that violating affirmative rules requires a negation, producing both the choice bias and performance costs. If that were the case, we might find more violations and superior violation performance with negated rules, as violating negated rules should reduce the ironic effects (Rück et al., 2021). Future research should, therefore, explore this intriguing intersection of nonconformity and rule formulation.…”
Section: Discussionmentioning
confidence: 99%
“…To make a choice, the participants pressed 1, 3, 7 or 9 on the number pad, corresponding to the position of the four words on the screen: lower left, lower right, upper left, and upper right, respectively. We have used this type of response mapping in other experiments in our lab (e.g., Rück et al, 2021 ) and find that participants experience little difficulty in mapping the location of the stimuli on the screen to the respective locations of the response keys.…”
Section: Methodsmentioning
confidence: 99%